The method to increase an adequacy and exactitude of the tracking of controlled airplane flight - Васильєв, В. М. (Proceedings of National Aviation University (archive), 2003)
The method to increase the adequacy and exactitude of trajectory estimates for tracking of controlled flight is proposed. The method of a solution of a non-linearity problem is also offered when imitate in trajectory estimation algorithm a control signal which includes nonlinear functions of restriction. The results of computer simulation are demonstrated